The Resolution of Technical Default. - Beneish, Messod D.; Press, Eric (The Accounting Review, 1995)
Examines whether the consequences arising from renegotiation of lending agreements are priced in the market. Technical default; Wealth losses from higher costs of borrowing and restrictions on firms' opportunities; Stock price declines; Debt covenant violation.